Leverage, Accounting Conservatism, and Tax Avoidance: The Moderating Role of Sales Growth Capability - Budiadnyani, Ni Putu; Aprilyani Dewi, Putu Pande R.; Jaya Kusuma, Putu Sri Arta (Universitas Swadaya Gunung Jati, 2025)
The majority of a nation's fiscal revenue comes from taxes, and both the academic and practical communities are paying close attention to tax evasion tactics. Nonetheless, a company's profitability and cash flows can be greatly impacted by tax charges in its accounting, which strongly encourages management to use tax evasion techniques. Understanding how these factors interact to influence a firm's financial decisions, especially with regard to tax tactics, requires analyzing the link between leverage, accounting conservatism, and tax avoidance with sales growth capability as a moderating variable. The study was conducted on all Food and Beverage Subsector Companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022 using the IDX's official website. Purposive sampling was used to determine the study's sample. The statistical program SPSS for Windows is used in this study to analyze data using both Linear Regression and Moderated Regression Analysis (MRA). The findings support earlier studies by indicating that leverage has a favorable and significant impact on tax evasion. The study did discover, however, that tax evasion methods are not directly and significantly impacted by accounting conservatism. The findings show that the impact of leverage on tax evasion can be amplified by sales growth, indicating a compounding effect.